THEORETICAL SOLUTION AND ITS CORRECTION OF THERMAL BUCKLING CRITICAL TEMPERATURE FOR CYLINDRICAL THIN-SHELL - WANG ZeWu; LI YaoZhou; XIA LiangZhi; SUN JiaLin (Jixie qiangdu)
For solving the inconsistence problem among existing theoretical solutions of the critical temperature for cylindrical thin-shell,in this paper,the theoretical solution of critical temperature was firstly deduced for a cylindrical thin-shell subjected to a uniform temperature rise based on Donnell equation. And then the numerical solutions of the flat-plate and the cylindrical shell were constructed separately. Lastly,comparison analysis between the theoretical solution and numerical solution was carried out,and the exact solution was obtained by introducing a modified coefficient. The study work will benefit to scientifically design related thin-shell structures in the future.